I am surrounded by death: death as a defining psychic issue within a relational psychoanalytic engagement and the impact of the therapist’s relationship with death - Zelda Gillian Knight (Research in Psychotherapy, 2019)
Taking inspiration from Frommer, this paper is part of a shift towards incorporating death as a defining psychic issue. With a sense that I am surrounded by death, the author presents two brief vignettes of clinical cases to illustrate the impact of the therapist’s relationship with death on the therapeutic process. Each case shows a different level of engagement with the client when the focus is on death-talk, and reflects, on the one hand, the therapist’s ability and readiness to work with death as an object of analysis, and on the other hand, the therapist’s lack of processing of experiences of death of others, and the resultant failure to successfully work with death in analysis. The one case is arguably more successful therapeutically than the other, and highlights some issues that come into play in the light of the therapist’s relationship with death. These issues are: i) the importance of the therapist’s development with regards to processing experiences of death and dying cannot be underestimated when working with death as an object of scrutiny; ii) empathy remains core to the process and getting in touch with how the client experiences the death of the other. Without recognition, however, no (grief) work can begin. The therapist needs to psychologically recognise the other to be able to connect to, and empathize with, the clients process; iii) the impact of the death of the other often transforms into the work of the impact of the death of self; iv) if clients have a sense that the therapist knows what they are speaking about because the therapist has done some of the work of making meaning of death, clients may feel more confident in working with death as an object of analysis.